Effect of traditional Chinese exercise on older patients with diabetes mellitus: a systematic review and meta-analysis of randomized controlled trials - Liu, Weimin; Che, Chong Chin; Chui, Ping Lei; Ma, Zifeng; Chen, Jing (Frontiers in Endocrinology, 2025)
ObjectiveThis systematic review and meta-analysis aimed to evaluate the effects of traditional Chinese exercises (TCEs) on blood glucose, glycosylated hemoglobin (HbA1c), body mass index (BMI), and health-related quality of life in older patients with diabetes mellitus (DM).MethodsDatabase searches were systematically conducted across multiple platforms. The review adhered to PRISMA guidelines, utilizing the Cochrane Risk of Bias Assessment Tool to gauge literature quality. Review Manager 5.3 was employed for data evaluation, calculating mean differences to ascertain pooled effect sizes.ResultsThis study encompassed 11 randomized controlled trials involving 944 individuals. The results showed that TCEs reduced fasting blood glucose (-0.76, 95% CI [-1.14, -0.38], P = 0.0001), HbA1c (-2.64, 95% CI [-4.81, -0.47], P = 0.02), and BMI (-0.83, 95% CI [-1.42, -0.24], P = 0.006), and improved health-related quality of life. Among the various forms of TCEs, Baduanjin (BDJ) appeared particularly beneficial.ConclusionsTraditional Chinese exercises can improve blood glucose levels, BMI and quality of life-related indicators to varying degrees in older diabetes patients, and may be a useful complementary therapy for this population.